Pengaruh Metode Discrete Trial Training (DTT) Terhadap Peningkatan Perbendaharaan Bahasa Bicara Pada Anak Retardasi Mental Di SLB Yaat Surakarta - Wiwik Setyaningsih; Dodiet Aditya Setyawan; Sudarman Sudarman (Interest : Jurnal Ilmu Kesehatan, 2017)
Abstract: Discrete Trial Training Methods, Language Vocabulary, Mental Retardation. Language plays an important role in the delivery of ideas, thoughts, and feelings of a person on others. But the delivery of ideas would be disturbed if the child is impaired in vocabulary, and it can occur in conditions of mentally retarded children. This research aimed to analyze the effect of the Discrete Trial Training (DTT) method to increase the vocabulary of speech in children with Mental Retardation in SLB YAAT Surakarta. This research uses experimental design of an activity to experiment aimed to determine the effect of the treatment that given using design of pre and post test only design, which will be held in SLB YAAT Surakarta, with the sampling technique used purposive sampling technique is determined by considering the purpose of research based on criteria which decided. The instrument which is used in this study were (collecting data) using instrument Assessment of Children's Language Comprehension (ACLC). From the test results of the data analysis by paired sample t-test on the variable of vocabulary in the pre-test and post-test had mean (average) and standard deviation of 0.20068-145 while the p-value (sig.) = 0.000> 0.05, in the two critical elements of variables or two important elements in the pre-test and post-test had a mean (average) and standard deviation of 9.71431 -22.33 while the p-value (sig.) = 0.000> 0.05. In the three critical elements of variables or three important elements in the pre-test and post-test had a mean (average) and standard deviation -17.00 16.43168 whereas the p-value (sig.) = 0.000> 0.05. While in the four critical elements of variables or four important elements of the pre-test and post test had a mean (average) and standard deviation 12.33 14.06471 whereas the p-value (sig.) = 0.000> 0.05. This shows that all the variables in this study showed that there is a significant effect of increasing their vocabulary and speech in children with mental retardation before and after exercise using DTT in SLB YAAT Surakarta.